Customer's satisfaction towards quality service and facilities in theme park / Farhana Syuhada binMohd Faidzul and Mohd Salim Jasiman - Mohd Faidzul, Farhana Syuhada; Jasiman, Mohd Salim (2019)
Theme Park is a large public entertainment permanent area. The major problem is climate that be most important factors influencing park attendance. Weather and climate are therefore the key issues to deal with. The proposed research has been selected at Movie Animation Park Studios (MAPS). The objective of the research is to determine the customer's satisfaction towards quality service and facilities provided in Movie Animation Park Studios (MAPS) and to rank the most popular quality service and facilities provided in Movie Animation Park Studios (MAPS). The data collection that able to gather the required respondents by usage of stratified random sampling that has been carried out. The descriptive and crosssectional studies and quantitative data is by using Statistical Package of Social Science (SPSS) has been selected in performing data analysis. The finding obtained showed a wide choice of customer's satisfaction towards staff attitude and toward service and facilities provided has conclude that all the variable has positive relationship.